A new species of Manlaya (Hymenoptera: Baissidae) from the Lower Cretaceous Shouchang Formation, Eastern China - Álvarez-Parra, Sergio; Huang, Di-Ying (Zootaxa, 2024)
Baissid wasps (Hymenoptera: Baissidae) represent a family within the superfamily Evanioidea composed of 36 species in seven genera restricted to a period spanning from the Berriasian (earliest Cretaceous) to the Turonian (early Late Cretaceous). The status and rank of the family have been changing over time, and recent phylogenetic analyses indicate that Baissidae may be paraphyletic to Aulacidae + Gasteruptiidae. The genus Manlaya Rasnitsyn, 1980 is the most diverse and widespread in the family, including representatives from western and eastern Laurasia. Here, we describe Manlaya minima sp. nov. from the Lower Cretaceous Shouchang Formation (Zhejiang Province, China). The new species has elbowed second medial cell, similar to Electrobaissa Engel, 2013, although the rest of the characters match with Manlaya, indicating that this character might be related to interspecific variability rather than differences between genera. The co-occurrence of Manlaya in the contemporaneous Shouchang Formation and the Jehol biota may point to a connection between the two entomofaunas. A key to the species of the family Baissidae from China is provided.